FRAKSI SERAT SILASE KULIT BUAH KAKAO DENGAN PENAMBAHAN LEVEL TEPUNG JAGUNG DAN LAMA FERMENTASI YANG BERBEDA - Mayangsari, Ismi; Harahap, Anwar Efendi; Zumarni, Zumarni (Universitas Djuanda Bogor, 2021)
One alternative in reducing feed production costs is by utilizing the waste of cocoa pods (Theobroma cocoa L). This study aims to determine the cocoa fruit silage fraction by adding different levels of corn flour and fermentation time. The method used in this study is an experimental method with a completely randomized design (CRD) factorial pattern consisting of 2 factors with 3 replications namely Factor A = Level of Corn Flour, A1 = 0% without Corn Flour, A2 = 7% Corn Flour, A3 = 14% Corn Flour. Factor B = Length of fermentation, B1 = Fermentation 0 days, B2 = Fermentation 14 days, B3 = Storage 28 days. The results showed that the duration of fermentation had a significant effect(P<0,05)on the content of NDF, ADF, cellulose, hemicellulose and lignin of cocoa peel. The conclusion of this study that the treatment of 14% corn flour and 28 days fermentation time is the best treatment because it can reduce NDF%, ADF% and Lignin% silage of cocoa pods